2017
DOI: 10.1177/2050312117697505
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a novel technique in airway clearance therapy – Specific Cough Technique (SCT) in cystic fibrosis: A pilot study of a series of N-of-1 randomised controlled trials

Abstract: Objectives:The aim of this pilot study was to evaluate the efficacy, safety and participants’ perception of a novel technique in airway clearance therapy – specific cough technique in cystic fibrosis.Methods:We conducted randomised controlled individual trials (N-of-1 randomised controlled trials) in six adults. Each trial included 8 weeks of treatment with two interventions each week, one with specific cough technique and one with forced expiration technique. The efficacy was investigated by a blinded assesso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Participants rinsed their mouth with water, before careful instructions were given on how to produce sputum from a deep cough, using the huff cough method [29]. Participants took three deep maximal breaths, before coughing as hard and as deeply as possible in a standing position.…”
Section: Methodsmentioning
confidence: 99%
“…Participants rinsed their mouth with water, before careful instructions were given on how to produce sputum from a deep cough, using the huff cough method [29]. Participants took three deep maximal breaths, before coughing as hard and as deeply as possible in a standing position.…”
Section: Methodsmentioning
confidence: 99%
“…It is therefore important that clinicians prescribing these devices base their judgement on the published clinical evidence of efficacy. Further, patient selection along with proper instruction of how to use the device optimally, including performing effective huffcoughs [123][124][125] is important to optimize therapeutic effect. Finally, this review has highlighted that clinical investigations have thus far been focused on patients with COPD/ chronic bronchitis.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study we performed a series of N-of-1 randomized, controlled trials and have reported on the individual efficacy, safety and participants’ perceptions of a novel ACT–Specific Cough Technique (SCT) compared to Forced Expiration Technique (FET) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The objective of the present secondary analysis of the prior study [ 8 ] was to assess the effectiveness of the intervention, by evaluating whether participation in the trial led to changes in HRQoL and in particular, clinical meaningful changes in CFQ-R-Respiratory Symptoms Scores (CFQ-R-RSS). A second aim was to examine potential associations between HRQoL and other clinical outcomes, such as sputum production and pulmonary function.…”
Section: Introductionmentioning
confidence: 99%